Education and Psychosocial Factors Predict Odds of Death After Transfer to Adult health Care in Pediatric Liver Transplant Patients. Issue 5 (27th June 2022) - Stevens, James P.; Gillespie, Scott; Hall, Lori; Tisheh, Julia; Ford, Ryan; Gupta, Nitika A.
Abstract : Objectives: To analyze demographic, psychosocial, and clinical factors in pediatric liver transplant recipients for their association with death or loss to follow up in adulthood. We aimed to better understand known health disparities in transplant outcomes and identify potentially modifiable risk factors prior to transfer. Methods: A retrospective cohort study of children who underwent liver transplantation at a large tertiary transplant center and were transferred to adult care between 2000 and 2015. Results: During the study period, 101 qualifying patients were transferred. Ninety-three individuals followed with an adult provider, while 8 were lost to follow up. In total 23 of 93 patients died after transfer (24.7%). Several childhood factors were associated with adult death: Black race [odds ratio (OR) 6.59, P < 0.001]; psychiatric illness or substance use (OR 2.81, P = 0.04); failure to graduate high school before transfer (OR 9.59, P < 0.001); posttransplant tacrolimus medication-level variability index >2.5 (OR 5.36, P = 0.04); provider documentation of medication nonadherence (OR 4.72, P = 0.02); acute cellular rejection (OR 4.44, P = 0.03); the presence of diabetes mellitus (OR 5.71, P = 0.001), and chronic kidney disease (OR 2.82, P = 0.04). Failure to graduate HS was associated with loss to follow up ( P < 0.001). On multivariate analysis, Black race, substance use, diabetes, and failure to graduate HS retained association with adult death (each P < 0.05). Conclusions: Complex, intertwined patient characteristics are associated with increased odds of death in pediatric liver transplant recipients transferred to adult care. Early recognition of high-risk patients and intervention for modifiable factors, such as improved HS graduation and substance use prevention, may improve long-term outcomes.